THE INFLUENCE OF INTERPERSONAL COMMUNICATION SKILLS AND DECISION MAKING ON FRONTLINERS' ABILITY TO HANDLE COMPLAINTS MEDIATED BY WORK STRESS LEVELS - Moch Aji Ramadhan; Addrie Frans Assa; Eka Desy Purnama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Employee productivity is influenced by Human Capital and the role of frontliners in interpersonal communication to handle complaints. Skills, decision-making, and work stress levels affect customer service effectiveness. This study aims to analyze the influence of interpersonal communication skills, decision-making, and work stress levels on frontliners' ability to handle complaints, as well as the mediating role of work stress. This research uses a quantitative approach with a survey method through questionnaires distributed to 41 employees of PT Wahana Ottomitra Multiartha, Tbk in the Kalimantan and Sulawesi regions, selected using simple random sampling. The data were analyzed using validity, reliability tests, and multiple linear regression with classical assumption tests (normality, multicollinearity, and heteroscedasticity) to examine the relationships between interpersonal communication skills, decision-making, work stress levels, and frontliners' ability to handle complaints. The results show that interpersonal communication skills have a positive effect on frontliners' ability to handle complaints (Reg. Coeff. = 0.225, Sig = 0.007). Decision-making also has a positive effect on frontliners' ability (Reg. Coeff. = 0.627, Sig = 0.000). Conversely, work stress levels negatively affect frontliners' ability (Reg. Coeff. = -0.786, Sig = 0.000). Interpersonal communication skills and decision-making increase work stress levels (Reg. Coeff. = 0.435, Sig = 0.002 and Reg. Coeff. = 0.411, Sig = 0.000), which then mediates the influence of these two factors on frontliners' ability to handle complaints (Sig = 0.000). This study concludes that interpersonal communication skills and decision-making enhance frontliners' ability to handle complaints, while work stress has a negative impact and acts as a mediator between these two factors